Silver Trimolybdate (Ag2Mo3O10.2H2O) Nanorods: Synthesis, Characterization, and Photo-Induced Antibacterial Activity under Visible-Light Irradiation - Maria Karollyna do Nascimento Silva Leandro; João Victor Barbosa Moura; Ana Carolina Justino de Araújo; Priscilla Ramos Freitas; Cicera Laura Roque Paulo; Amanda Karine de Sousa; Janaina Esmeraldo Rocha; Lívia Maria Garcia Leandro; Rakel Olinda Macedo da Silva; Clenilton Costa dos Santos; Jaime Ribeiro-Filho; Cleânio da Luz Lima; et al. (Bioinorganic Chemistry and Applications)
The present study reports the synthesis, characterization, and antibacterial properties of silver trimolybdate (Ag2Mo3O10.2H2O) nanorods. The synthesis was performed using a conventional hydrothermal method. The sample was characterised by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, UV–Vis–NIR diffuse reflectance, thermogravimetric analysis (TGA), and differential scanning calorimeter (DSC). The direct antibacterial activity was evaluated using the microdilution method to determine the minimum inhibitory concentration (MIC). To assess the ability of Ag2Mo3O10.2H2O nanorods to modulate antibacterial resistance, the MIC of aminoglycosides was established in the presence of a subinhibitory concentration of this substance alone and associated with LED light exposure. The characterization of the sample indicated that the synthesis of silver trimolybdate generated nanometric crystals with rod-like morphology, without secondary phases. The treatment with Ag2Mo3O10.2H2O nanorods alone or combined with visible LED lights exhibited clinically relevant antibacterial activity against both Gram-negative and Gram-positive bacteria. This nanostructure presented a variable antibiotic-modulating action, which was not improved by visible LED light exposure. Nevertheless, LED lights showed promising antibiotic-enhancing activities in the absence of Ag2Mo3O10.2H2O nanorods. In conclusion, silver trimolybdate dihydrate nanorods have antibacterial properties that can be photocatalysed by visible-light exposure. While showing the potential use to combat antibacterial resistance, the simultaneous combination of silver trimolybdate, visible LED lights, and antibacterial drugs should be carefully analysed to avoid antagonist effects that could impair the effectiveness of antibiotic therapy.